Macrolide resistant Streptococcus pyogenes in Iceland. Epidemiological and molecular study - Sara Björk Southon 1991- (2017)
Streptococcus pyogenes (group A streptococcus, GAS) is an important cause of morbidity and mortality in humans worldwide. Penicillin is the standard of care for treating GAS infections and all GAS strains are susceptible to penicillins, but macrolides are the secondary line of treatment for individuals allergic to penicillins. Resistance to antibiotics, primarily macrolides (e.g. erythromycin), is an increasing concern in the treatment of GAS infections. The first two macrolide resistant GAS epidemics in Iceland have been investigated with pulsed field gel electrophoresis (PFGE). The results suggested that the macrolide resistant isolates were highly clonal populations which sparked an interest to whole-genome sequence all macrolide resistant GAS isolates available at the Department of Microbiology at the Landspítali University Hospital of Iceland. The main aims of this study were to investigate epidemiology of macrolide resistant isolates with emphasis on relation to specific clones and investigate genetic relationship among the resistant isolates, the mechanism that causes macrolide resistance in GAS in Iceland and the expression of the most prevalent genes that encode for macrolide resistance in the isolates. Laboratory information system at the Department of Microbiology at the Landspítali University Hospital of Iceland was used to get the data needed. Only patient samples were used. Erythromycin resistant GAS that had been identified and stored at the Department of Microbiology at the Landspítali University Hospital of Iceland from the years 1998-2016 were sent to Houston Methodist Research Institute for whole-genome sequencing in Illumina NextSeq500 sequencer. Gene expression analysis of the most prevalent macrolide resistance genes found among the GAS population, was performed for 15 isolates, 5 from each emm-type with quantitate real time PCR (qRT-PCR). Gene expression of the most prevalent macrolide resistance genes, with erythromycin induction was performed for 4 isolates. To see if MICs for the 15 ...